Analysis of Factors Affecting the Rate of Latent Tuberculosis Infection and Management in Pediatrics - Hee Won Ma; Hee Soo Lee; Ji Young Ahn (MDPI AG, 2022)
The incidence of tuberculosis remains high in South Korea; the management of latent tuberculosis infection (LTBI) has become the prime target for reducing the infection rate. The management of pediatric LTBI is especially crucial because children can serve as a long-term source of infection upon developing active tuberculosis. Therefore, it is important to assess pediatric LTBI using contact investigation and follow-up. We conducted a retrospective study on children aged between 0 and 18 years who visited our hospital for tuberculosis contact screening from February 2012 to February 2021. Tuberculosis index cases and their clinical characteristics were also reviewed retrospectively. A total of 350 children were investigated, and 68 of 247 (27.5%) were diagnosed with LTBI. The rate of LTBI (r = 7.98, p < 0.001) and the risk of loss to follow-up (r = 27.038, p < 0.001) were higher in cases with close household contact. Sputum (r = 10.992, p < 0.001) and positive acid-fast bacillus (AFB) stain (r = 4.458, p = 0.001) in tuberculosis index cases were related to the diagnosis of LTBI in pediatric contacts. Active management is needed for tuberculosis screening in pediatric contacts, especially when the contacts are older and the index case is within the family, and when the index case has sputum and has tested positive for AFB smear.